Dynamic Electricity Price Guidance Analysis of Urban Electric Vehicle Based on Actual Data Drive. Issue 1 (January 2020) - Duanchao, Li; Han, Su; Haiwei, Wang
Abstract: Establishing a dynamic electricity price to guide the charging behavior of car owners can better help electric vehicles (EV) to participate in peak shaving and valley filling of the grid. On the basis of this, a dynamic electricity price mechanism for electric vehicle charging stations in city was proposed in this paper.It was aimed at the distribution network where residential areas are located and mean to improve the ability of EV to cut peaks and fill valleys. Firstly, the load characteristics of residential areas were analyzed, in addition, the load status of the distribution network in the area before and after the EV charging station connected in were compared. Secondly, according to the proposed dynamic electricity price calculation process and related function based on the TOU (time-of-use) electricity price for electric vehicle charging station, the dynamic price of the day was established, then in order to predict the power load after the dynamic electricity price is implemented, the corresponding model based on the residential load elastic demand matrix was established. Finally, taking the actual data of a certain district near residential area in Anhui province and an electric vehicle charging station as an example, formulated the targeted dynamic electricity price and further verified the feasibility and effectiveness of the study.